Terrorism as cancer: how to combat an incurable disease - Price, Bryan C. (Terrorism and political violence, 2019)
This paper provides an alternative framework that conceptualizes the threat posed by terrorism based on an epidemiological approach that views it as a chronic disease like cancer rather than as a military, ideological, or socio-economic problem. After highlighting the similarities in the causes, behavior, treatments, and challenges of combating terrorism and cancer, this paper presents a staging system policymakers can use to educate the public and allocate counterterrorism resources more efficiently. This approach encourages policymakers to see terrorism for what it is (an all but inevitable facet of modern life that can be managed but never fully eliminated), and not what they wish terrorism to be (a national security problem that can be solved, defeated, or vanquished). It provides policymakers with a useful model to conceptualize the threat and treat terrorism in a comprehensive manner, from preventing future attacks to effectively responding to them when they will inevitably occur.